SERVICE QUALITY AND CUSTOMER SATISFACTION: EVIDENCE FROM ABUJA ELECTRICITY DISTRIBUTION COMPANY (AEDC) CONSUMERS IN MINNA METROPOLIS - Tamu, Jagaba Shuaibu; Babandako, Abdullahi Yusuf; Masud, Abdullahi (Kashere Journal of Management Sciences, 2025)
The Nigerian power sector is characterized by several challenges, including inconsistent supply from the country’s connection to the grid, slow personnel fault-clearing responses, poor staff-customer relationships, irrational electricity pricing and inaccurate billing, difficulties collecting payments due to subpar bank services and/or remote payment centers, and incorrect customer disconnection. This study examined service quality and customer satisfaction: evidence from Consumers of Abuja Electricity Distribution Company (AEDC) in Minna metropolis. This study adopted a quantitative survey research method. The instrument used was structured questionnaire which was measured using 5-point Likert scale. AEDC customers in Minna metropolis make up the research population. Three hundred (300) electricity consumers in Minna metropolis were selected using purposive non-probability sampling technique. The data collected through questionnaire were analyzed using Multiple Regression analysis. Findings from the five hypotheses revealed that tangibility, reliability, responsiveness and empathy have significant effect on customer satisfaction (P = 0.00 < 0.05) while only assurance have no significant effect on customers satisfaction (P = 0.824 > 0.05). Thus, we conclude that service quality has significant effect on customers’ satisfaction. It is recommended that AEDC should enhance the services it provides to its customers by providing consistent power supply and responding promptly to customer complaints and suggestions.